Characterization of agr Groups of Staphylococcus pseudintermedius Isolates from Dogs in Texas - Sara V. Little (American Society for Microbiology, 2019)
ABSTRACT Staphylococcus pseudintermedius is an important canine pathogen implicated in an increasing number of human infections. Along with rising levels of methicillin and multidrug resistance, staphylococcal biofilms are a complicating factor for treatment and contribute to device, implant, and surgical infections. Staphylococcal virulence, including biofilm formation, is regulated in part by the quorum sensing accessory gene regulator system (agr). The signal molecule for agr, known as the autoinducing peptide molecule, contains polymorphisms that result in the formation of distinct groups. In S. pseudintermedius, 4 groups (i.e., groups I, II, III, and IV) have been identified but not comprehensively examined for associations with infection type, virulence factor carriage, or phylogenetic relationships—all of which have been found to be significant in S. aureus. In this study, 160 clinical canine isolates from Texas, including isolates from healthy dogs (n = 40) and 3 different infection groups (pyoderma, urinary tract, and surgical, n = 40 each), were sequenced. The agr group, biofilm-producing capabilities, toxin gene carriage, antimicrobial resistance, and sequence type (ST) were identified for all isolates. While no significant associations were discovered among the clinical infection types and agr groups, agr II isolates were significantly less common than any other group in diseased dogs. Furthermore, agr II isolates were less likely than other agr groups to be multidrug resistant and to carry toxin genes expA and sec-canine. Fifty-two (33%) of the 160 isolates were methicillin resistant, and the main sequence types (ST64, ST68, ST71, ST84, ST150, and ST155) of methicillin-resistant strains of S. pseudintermedius (MRSP) were identified for the geographic region. IMPORTANCE Staphylococcus pseudintermedius is an important disease-causing bacterium in dogs and is recognized as a growing threat to human health. Due to increasing multidrug resistance, discovery of alternative methods for treatment of these infections is vital. Interference with one target for alternative treatment, the quorum sensing system agr, has demonstrated clinical improvement of infections in S. aureus animal models. In this study, we sequenced and characterized 160 clinical S. pseudintermedius isolates and their agr systems in order to increase understanding of the epidemiology of the agr group and clarify its associations with types of infection and antimicrobial resistance. We found that isolates with agr type II were significantly less common than other agr types in diseased dogs. This provides valuable information to veterinary clinical microbiologists and clinicians, especially as less research has been performed on infection associations of agr and its therapeutic potential in S. pseudintermedius than in S. aureus.